Effect of Monovalent and Divalent Salts on the Interfacial Tension of n-Heptane against Aqueous Anionic Surfactant Solutions - Jha, N.; Iglauer, Stefan; Sangwai, J. (American Chemical Society, 2018)
© 2017 American Chemical Society. A very low interfacial tension, γ, can be achieved between an oil phase and an aqueous solution containing anionic surfactant and salt at a very low concentration. This phenomenon can have potential applications in recovering residual oil from the reservoir through low salinity-low surfactant enhanced oil recovery flooding. Measurements of γ between n-heptane and aqueous solution of anionic surfactants in the concentration range of 0.141-2.167 mM and salts in the concentration range of 9.010-119.780 mM at 313.15 ± 0.1 K have been carried out. The experimental results show that the value of γ falls to a lowest value at a temperature above the Krafft point when the concentration of anionic surfactants [sodium dodecyl sulfate (SDS) and dioctyl sulfosuccinate sodium salt (AOT)] is increased up to a maximum surface excess concentration in an aqueous solution in the presence of monovalent [sodium chloride, (NaCl)] and divalent [calcium chloride, (CaCl2)] salts in the low concentration range. To understand and adequately capture the reduction of γ in such systems with n-heptane as an oil phase, a simplistic model is being proposed here. This model is an extension of the Petersen and Saykally model which was earlier developed to capture the Jones-Ray effect.